Chapter La Facoltà di Scienze politiche “Cesare Alfieri” dalla crisi al primato (1938-2001) - Rogari, Sandro (Firenze University Press, 2025)
The forced fusion into the University of Florence along the headmastership of Rodolico compelled the new Faculty to reform its educational system and to follow the Fascist doctrine 1938-1943. As a consequence of the regime’s falling, opened a season of uncertainty on the future of Faculties of political sciences. Hard were the thrusts to close them for their deep compromise with Fascism, 1943-1948. The turning point arrived with Maranini dean and his regeneration of political sciences 1949-1968. That was the golden age of “Cesare Alfieri”. Then, the Faculty ought to Sartori the new educational system split in five specializations. A national law (1980) created the Department as new organization of research. (1969-2001). The Faculty became a mass educational institution.